2008
DOI: 10.3171/jns/2008/109/11/0856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a side population of astrocytoma cells in response to temozolomide

Abstract: Knockdown of ABCG2 transporters did not abrogate the SP cell response to temozolomide. Upregulation of several other ABC drug transporter genes is proposed to account for this chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 58 publications
4
55
1
Order By: Relevance
“…With regards to the sorting techniques, there are two basic methods available, one is immunomagnetic beads or fluorescent activated cell sorting (FACS) based on the surface marker CD133; and the other method is the SP cell sorting technique based on a drug-resistant gene, such as an ATP-binding cassette or a multidrug resistance gene (MDR) (17,20). In either case, the supposed BGSCs are sorted, then identified and cultured.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the sorting techniques, there are two basic methods available, one is immunomagnetic beads or fluorescent activated cell sorting (FACS) based on the surface marker CD133; and the other method is the SP cell sorting technique based on a drug-resistant gene, such as an ATP-binding cassette or a multidrug resistance gene (MDR) (17,20). In either case, the supposed BGSCs are sorted, then identified and cultured.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms are thought to account for such resistance, and DNA repair-related genes such as MGMT, MSH2, and MSH6 have been identified as key players involved in tumor survival after treatment with alkylating agents (1,(3)(4)(5). Moreover, a small population of cells with self-renewal capacity and immature phenotype, called "glioma stem cells," have been shown to be highly resistant to chemotherapy and radiation (6)(7)(8). In fact, several authors have hypothesized that these tumor stem cells are the source of the recurrent tumors after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several authors have hypothesized that these tumor stem cells are the source of the recurrent tumors after treatment. The phenotype, ex vivo assays and markers that define such stem cells are debated topics (6)(7)(8)(9). Bao et al used CD133 as a putative marker for characterization of these treatmentresistant cells in the setting of radiotherapy (8).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies revealed that cellular stresses like drug exposure (Chua et al, 2008;Calcagno et al, 2010;Fong et al, 2010), hypoxia (Bar et al, 2010) and UV lighting (Liang et al, 2010) enriched for a CSC phenotype in cancer cell lines. In this study, we detected 1% cells positive for SP in the primary line SW1116 and observed a remarkable increase to 6%, 44% and 97% after HCPT treatment to 3 months, 6 months and 41 years, respectively.…”
Section: Discussionmentioning
confidence: 99%